Proposing accountability index for zakat institution / Rini Rini, Ari Purwanti and Wilda Farah - Rini, Rini; Purwanti, Ari; Farah, Wilda (Faculty of Accountancy, 2019)
This study aims to determine and analyze the purpose of financial statements, indicators of accountability, and what are the requirements of financial statements at zakat institutions. Research method of this study used qualitative research with critics paradigm. Data were obtained by Interview with financial division of ZI, Questionnaire to muzakki, and FGD with zakat expert and scholar. The sampling method used is convenience sampling. The result shows Islamic accountability index for the zakat institutions consists of six themes taken from previous research. the highest weight is in dimension 1 of Finance with a weight value of 29.38%, followed by dimension 2 of performance of 16.17%, then dimension 5 of governance is 14.87%, then dimension 3 is public information of 14.73%, then the dimension 6 is compliance with sharia law and other regulations by 14.01%, and the lowest is the dimension 4 which is Engagement/interaction by 10.84%.